Exploring the Nexus of lower extremity proprioception and postural stability in older adults with osteoporosis: a cross-sectional investigation - Ahmad, Irshad; Reddy, Ravi Shankar; Alqhtani, Raee S.; Tedla, Jaya Shanker; Dixit, Snehil; Ghulam, Hussain Saleh H.; Alyami, Abdullah Mohammed; Al Adal, Saeed; Jarrar, Mohammad A. M. (Frontiers in Public Health, 2023)
Background Osteoporosis, characterized by reduced bone mass and micro-architectural deterioration, poses a significant public health concern due to increased fracture susceptibility. Beyond bone health, this cross-sectional study aimed to assess and compare lower extremity proprioception and postural stability in individuals with and without osteoporosis and to explore their correlation within the osteoporosis group. Method In this prospective cross-sectional study, 80 participants were divided into two groups: osteoporosis (n = 40) and control (n = 40). The demographic characteristics and clinical parameters of the participants were as follows: Age (years) – Osteoporosis group: 65.04 ± 4.33, Control group: 65.24 ± 4.63; Sex (%) – Osteoporosis group: Male 30%, Female 70%; Control group: Male 30%, Female 70%; Body mass index (kg/m2) – Osteoporosis group: 23.7 ± 3.2, Control group: 24.5 ± 4.6; T-score (Lumbar) – Osteoporosis group: −2.86 ± 1.23, Control group: 0.27 ± 0.58; T-score (hip) – Osteoporosis group: −2.28 ± 0.79, Control group: 0.68 ± 0.86. Joint Position Sense (JPS) at the hip, knee, and ankle was assessed using a digital inclinometer, and postural stability was measured using computerized force platforms. Result Osteoporosis participants exhibited higher errors in hip (5.63° vs. 2.36°), knee (4.86° vs. 1.98°), and ankle (4.46° vs. 2.02°) JPS compared to controls. Postural stability measures showed increased anterior–posterior sway (10.86 mm vs. 3.98 mm), medial-lateral sway (8.67 mm vs. 2.89 mm), and ellipse area (966.88 mm2 vs. 446.19 mm2) in osteoporosis participants. Furthermore, correlation analyses within the osteoporosis group unveiled significant positive associations between lower extremity proprioception and postural stability. Specifically, hip JPS exhibited a strong positive correlation with anterior–posterior sway (r = 0.493, p = 0.003), medial-lateral sway (r = 0.485, p = 0.003), and ellipse area (r = 0.496, p < 0.001). Knee JPS displayed a moderate positive correlation with anterior–posterior sway (r = 0.397, p = 0.012), medial-lateral sway (r = 0.337, p = 0.032), and ellipse area (r = 0.378, p < 0.001). Similarly, ankle JPS showed a moderate positive correlation with anterior–posterior sway (r = 0.373, p = 0.023), medial-lateral sway (r = 0.308, p = 0.045), and ellipse area (r = 0.368, p = 0.021). Conclusion These findings underscore the interplay between proprioceptive deficits, compromised postural stability, and osteoporosis, emphasizing the need for targeted interventions to improve fall prevention strategies and enhance the quality of life for individuals with osteoporosis.